The effect of COVID-19 pandemic in geriatric rehabilitation services in hospitalized patients - Setiono, Steven; Wahyuni, Luh Karunia; Kusumaningsih, Widjajalaksmi; Harini, Melinda; Kusumawardhani, Rizky; Sunarjo, Peggy; Laksmitasari, Budiati (AIP conference proceedings, 2023)
During the COVID-19 pandemic since March 2020 in Indonesia, inpatient geriatric rehabilitation services have some adaptations including telerehabilitation, no aerosol generating procedure, log-book for program evaluation, and caregiver as supervisor instead of therapists. The aim of this research was to know six-minutes walking test (6MWT) distance average and whether 6MWT procedure prior to discharge remains safe regarding services adjustment during pandemic. This study is a descriptive analytic study using a cross-sectional design and a retrospective cohort. The study was conducted in June 2020 until April 2021. The subjects were all the geriatric rehabilitation patients who meet the inclusion criteria. The functional status was measured using six-minute walking test before the patients were discharged. As many as 28 subjects were involved. The mean age of the subjects was 61.89 years with 75% (21 subjects) was male. The underlying disease mostly was diabetes mellitus. The vital signs were within normal limit before and after the test. The result of the six-minute walking test showed that the average walking distances were 196.34 meters with VO2max 69.98 kg/mL/minute and 2.82 METs. This study showed regarding to the changes, 6MWT is feasible to be done prior to discharge. Further studies are needed to confirm the effectiveness of those adaptive methods in improving patient’s independency in daily activity.